1999
DOI: 10.1073/pnas.96.21.12144
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous activation of metabotropic glutamate receptors in neocortical development causes neuronal calcium oscillations

Abstract: ] i increases in local cell clusters, and synchronous transients in cell pairs undergoing mitotic division (8). In the postnatal neocortex, coordinated [Ca 2ϩ ] i rises can occur in 3-100 adjacent neurons, termed neuronal domains (9). These spontaneous events are mediated by gap junctional communication (10) and appear to involve cell-to-cell diffusion of the second messenger inositol trisphosphate (9, 11). Neocortical domains apparently can occur independently of action potential activity, but their freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
87
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 48 publications
1
87
0
Order By: Relevance
“…The spontaneous cortical activities are assumed to differ. They are mediated by activation of metabotropic glutamate (20) or GABA A (21) receptors or by Ca 2ϩ mediated by IP 3 through gap junctions (23). In this study, we found that synchronized spontaneous Ca 2ϩ oscillations occurred in cortical neurons obtained from postnatal 2-3-day-old rats after 5 days of in vitro culture (DIV 5).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The spontaneous cortical activities are assumed to differ. They are mediated by activation of metabotropic glutamate (20) or GABA A (21) receptors or by Ca 2ϩ mediated by IP 3 through gap junctions (23). In this study, we found that synchronized spontaneous Ca 2ϩ oscillations occurred in cortical neurons obtained from postnatal 2-3-day-old rats after 5 days of in vitro culture (DIV 5).…”
Section: Discussionmentioning
confidence: 62%
“…In the cortex, it was reported that spontaneous oscillations were seen only in individual cells (20,21) from small groups consisting of 5-50 neurons (37) or in larger populations (24). The spontaneous cortical activities are assumed to differ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mGlu1 and mGlu5 utilize similar signal transduction pathways, activation of mGlu1 receptors elicits a single Ca 2ϩ peak (30) whereas mGlu5 activation leads to a marked oscillatory response in heterologous cells (30 -32) as well as neocortical, hippocampal (33), and spinal cord neurons (34). It has been estimated that 90% of the Ca 2ϩ oscillations that occur spontaneously in immature cortical neurons can be ascribed to mGlu5 receptors (33).…”
Section: Changes In Nuclear Camentioning
confidence: 99%
“…It has been estimated that 90% of the Ca 2ϩ oscillations that occur spontaneously in immature cortical neurons can be ascribed to mGlu5 receptors (33). Inasmuch as Ca 2ϩ oscillations can differentially affect gene expression (35), they play an important role in the control of developmental events.…”
Section: Changes In Nuclear Camentioning
confidence: 99%